(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
Financing of the Holy See, transparency of destination and patrimonial administration ABSTRACT: The essay analyzes the topic of the economic and financial management of the Holy See’s patrimony and in particular the reforms implemented during the pontificates of Benedict XVI and Francis which ensure greater transparency of financial operations. In carrying out its universal mission, the Church relies on transparent and efficient asset management. All those who manage the Church’s patrimony must administer it wisely, avoiding the performance of speculative operations in order to preserve the economic value of the assets, which are instrumental to all Church activities. Because of this, the Vatican judicial system has also been strengthened to prevent and eventually repress abuses in the management of ecclesiastical patrimony. It must be stressed, however, that, excessive garantism in the management of Vatican finances could risk hindering the Holy See’s activities. In this sense, the essay also reflects on the advisability of bypassing the ordinary system of financial transparency in peculiar circumstances in order to guarantee the Holy See’s evangelization activities. SOMMARIO: 1. Introduzione - 2. La gestione finanziaria - 3. Le norme di gestione patrimoniale della Santa Sede: dalla Pastor Bonus alla Praedicate Evangelium - 4. Riflessioni conclusive.